Tensions between inclusion and change in worldview education: can Joe F. Kincheloe's bricolage help teachers navigate them? - Andreassen, Øyvind Soltun; Doney, Jonathan (British journal of religious education, 2024)
This paper delineates tensions that arguably are inherent to integrative Worldview Education in plural societies, due to the subject's dual commitment to imperatives of inclusion and change. The imperative of inclusion stems from the subject's mandate to integrate the whole plurality of pupils in society, whereas the imperative of change stems from the subject's mandate to promote certain aims and values over others. The task of handling such tensions can be daunting, and teachers need resources that enable them to do so. The main aim of this paper is thus to provide a critical examination of the metaphor of bricolage, as it was conceptualised by Joe L. Kincheloe, in search of such resources. The examination points to the following chain of argument: (1) Kincheloe's bricolage contains its own tensions between inclusion and change, due to its application of multiple methods, methodologies, and perspectives, combined with a desire to promote social change. (2) There is a strong overlap between the two sets of tensions. (3) Teachers should be aware of the distinct political and philosophical underpinnings of Kincheloe's bricolage, and how these can create new tensions, possibly productive ones, if teaching and learning in Worldview Education is framed as bricolage work.